New embedding and staining systems PrestoCHILL and Presto stainer for application in the advancement of Mohs micrographic surgery. Issue 4 (2nd October 2017) - Orchard, GE; Shams, M; d'Amico, C; Wojcik, K; Ismail, F; Mohammad, M; Salih, R; Shams, F; Mallipeddi, R
Abstract: Background: Mohs micrographic surgery (MMS) involves evaluation of frozen tissue sections to determine complete circumferential and deep tissue margin clearance of skin tumours. PrestoCHILL and Presto stainer devices are two new innovative tools which bring benefits of automation, speed and efficiency to the preparation of frozen section analysis in MMS. The devices were assessed at Viapath's Tissue Science Mohs laboratory at Guy's Cancer Centre. Material and Methods: A total of 279 samples from 10 anatomically different facial sites. These included nose (95), lip (24), forehead (47), cheek (25), eyelids (34), temple (9), chin (15), ear (17), scalp (6) and neck (7). These were analysed using both devices simultaneously. Results: The PrestoCHILL device was measured for accuracy of tissue orientation by determining how many of the cases examined microscopically had complete margin and full epidermis preservation. The precision and reproducibility of the Presto stainer was evaluated by the consistency of achieving ideal standards of staining quality as defined by the department's internal quality control check, on stained sections examined and evaluated microscopically. The mean (standard deviation) score for accuracy for the PrestoCHILL across all tissue facial sites was 93.5 (11)%; the mean (standard deviation) score for precision/reproducibility of the Presto stainer was 96.5 (11)% (both p < 0.05). Conclusion: The devices combined offer an assured accuracy and precision performance, which is reproducible across all facial tissue types examined. The devices represent a key step forward in the introduction of improved automated embedding and staining procedures within MMS.